2020
DOI: 10.4258/hir.2020.26.3.220
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Digital Divide on the Adoption of Online Patient Portals for Self-Motivated Patients

Abstract: Online patient portals are web-based applications that give patients direct and secure 24-hour access to their Electronic Health Records. Through such portals, they can view information like laboratory results, medication history, and discharge summaries. Patients can also perform various activities, such as securely message their providers, request prescription refills, and schedule appointments [1]. Patient portal use can increase patient engagement [2-4] and thereby improve the quality of care provided to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We cannot determine other factors that contribute to the patients' perceived usability and self-efficacy after seeing their lab results online. Possible other determinants that may impact usability and self-efficacy are the quality of the portal, the motivation to use the internet for health improvement [31], and the way patients use their knowledge in relation to the doctor [32,33]. Regarding the patient portal itself, lab results need to be easily understandable [34], and technology needs to be easy to use [8,35].…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…We cannot determine other factors that contribute to the patients' perceived usability and self-efficacy after seeing their lab results online. Possible other determinants that may impact usability and self-efficacy are the quality of the portal, the motivation to use the internet for health improvement [31], and the way patients use their knowledge in relation to the doctor [32,33]. Regarding the patient portal itself, lab results need to be easily understandable [34], and technology needs to be easy to use [8,35].…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…One meta-analysis demonstrated that mean adoption rates for patient portal hovered around 52% with "real-world experiments" having a much lower adoption rate of 23%. 28 Patient portal adoption rates also vary by patient demographics and socioeconomic factors with patients who are female, white, and commercially insured having higher odds of using their patient portal. 29 Within our own community, 77% of eligible patients had an active patient portal reflective of high usage in our patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing portal inequities faced by all underserved patients requires addressing initial barriers related to digital divides due to lack of broadband Internet access, device access, and digital literacy. [28][29][30] With more recent data showing that LEP patients have close to equal rates of Internet access compared with the general population, addressing the remaining broadband access gaps is a critical step towards portal equity. 31 Policies investing in broadband infrastructure as well as subsidized Internet services address the need for access to the Internet, which is increasingly a social determinant of health (SDOH).…”
Section: Digital Access and Literacymentioning
confidence: 99%